Speak up guide: Bidayuh dialect - Abd Samad, Sabariah; Ibrahim, Imilia; James, Adjuelia; Omar, Sharifah Anom; Daud, Mohd Shamsul (Universiti Teknologi MARA, Kedah, 2018)
Sarawak is one of the state located in Borneo Island and considered the largest in Malaysia. The state consists of multiple tourist attractions including mountains, caves and beaches. Due to this fact, tourism has been the key economic activity for Sarawak. In 2017 alone, 4,856,888 tourists have visited Sarawak. In Sarawak, there are more than 40 sub ethnics. Each of these ethnics are special with their own language, culture and lifestyle. They are diversify by their locality as well as their sub ethnic. Generally, the diversity of the people with their own unique features are the main attraction to the state.It is an advantage for the tourist if they know a little bit of the local dialect. Although Sarawakian are able to converse in English and Malay language, their ability to convey important and interesting information might be limited. Especially if we are communicating with the older generations. Thus, the local language has become one of the strong element to fascinate tourist locally and internationally to explore more. The issue is, presently there is no handy guidebook for local language in Sarawak. Therefore, the “Speak Up Guide” would be of help to those who want to understand and communicate in the local dialect. The objective of this invention is to create a handy printed guidebook to be used by the tourist who wants to learn the local dialect. This version of the guide will cover Bidayuh dialect. Bidayuh people normally lives in the southern part of the state. Being called the “Land Dayak”, Bidayuh people are the second largest ethnic in Sarawak. Ability to speak in Bidayuh dialect would allow us to visit the non-conventional tourist attractions and learn more about the people and their culture. Novelty and uniqueness: This guidebook is unique as the first guidebook publish that cover Bidayuh dialect. Compared to a dictionary, this guidebook will cover a daily interaction used by the Bidayuh people. It is more fun to learn and interact with the local.